A antropologia de Edith Stein: entre Deus e a filosofia - Kusano, Mariana Bar (2009)
The purpose of this project is the study of Edith Stein s (1891-1942) philosophical and theological anthropology and its implications on pedagogy. In this sense, Stein s anthropology presents itself as a great effort to comprehend the human being s profound structure, considering the relations established with things, with other human beings and, finally , with God. Her analysis start based on Husserl s phenomenological method and, afterwards, are submitted to Tomas de Aquino s metaphisical indagations. On this movement between Husserl s phenomenology and Tomas de Aquino s metaphisics, Edith Stein describes the essencial constitution of the human being as constituent of body, soul and spirit as well as this essencial structure s individuation. Edith Stein s analysis on the human being comes from a pedagogical requirement and, for this reason, this project presents as a hypothesis the attempt to demonstrate how the anthropology of philosophical nature and the anthropology that lies on Revealed data can constitute as the fundaments of the pedagogy practice and theory. For that, many writings from the author and from scholars of the author have been studied in order to exemplify and confirm the analysis and interpretations on the subject-matter